Gene Therapy in Liver Ischemia and Reperfusion Injury - Ke, Bibo; Lipshutz, Gerald S.; Kupiec-Weglinski, Jerzy W. (Current Pharmaceutical Design, 2006)
Ischemia and reperfusion injury (IRI) is a prime antigen-independent inflammatory factor in the dysfunction of liver transplants. Despite improved allograft preservation and surgical techniques, IRI can still cause up to 10% of early orthotopic liver transplant failure, and can lead to a higher incidence of both acute and chronic graft rejection. Recent advances in gene transfer have resulted in a reduction or inhibition of liver IRI in several experimental models. This review summarizes the development of existing and potential approaches to human gene therapy. These studies aimed at ameliorating I/R injury are focused on the cytoprotective effects in transplant recipients by induction of anti-apoptotic or protective genes, immunoregulation of cytokines or blockade of signaling transduction pathway in graft cells. Although this review focuses on the application of viral mediated gene therapy, new non-viral gene transfer techniques, such as RNA interference (RNAi) application, are discussed. Future advances in gene therapy technology should result in fewer side effects, and thus more acceptable for clinical application, and more successful for organ transplantation.
Keywords: Costimulation